DIRS retrotransposons amplify via linear, single-stranded cDNA intermediates. Issue 8 (14th March 2020) - Malicki, Marek; Spaller, Thomas; Winckler, Thomas; Hammann, Christian
Abstract: The Dictyostelium Intermediate Repeat Sequence 1 (DIRS-1) is the name-giving member of the DIRS order of tyrosine recombinase retrotransposons. In Dictyostelium discoideum, DIRS-1 is highly amplified and enriched in heterochromatic centromers of the D. discoideum genome. We show here that DIRS-1 it tightly controlled by the D. discoideum RNA interference machinery and is only mobilized in mutants lacking either the RNA dependent RNA polymerase RrpC or the Argonaute protein AgnA. DIRS retrotransposons contain an internal complementary region (ICR) that is thought to be required to reconstitute a full-length element from incomplete RNA transcripts. Using different versions of D. discoideum DIRS-1 equipped with retrotransposition marker genes, we show experimentally that the ICR is in fact essential to complete retrotransposition. We further show that DIRS-1 produces a mixture of single-stranded, mostly linear extrachromosomal cDNA intermediates. If this cDNA is isolated and transformed into D. discoideum cells, it can be used by DIRS-1 proteins to complete productive retrotransposition. This work provides the first experimental evidence to propose a general retrotransposition mechanism of the class of DIRS like tyrosine recombinase retrotransposons.